2012
DOI: 10.1038/oncsis.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

MLK4β functions as a negative regulator of MAPK signaling and cell invasion

Abstract: Mixed lineage kinase (MLK) 4, or MLK4, is a member of the MLK family of mitogen-activated protein kinase kinase kinases (MAP3Ks). Typically, MAP3Ks function to activate the mitogen-activated protein kinase (MAPK)-signaling pathways and regulate different cellular responses. However, here we report that MLK4β, unlike the other MLKs, negatively regulates the activities of the MAPKs, p38, c-Jun N-terminal kinase and extracellular signal-regulated kinase, and the MAP2Ks, MEK3 and 6. Our results show that MLK4β inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…These results indicate that MLK4 has a suppressive effect on JNK and p38 activation in response to thermostress, and ERK, JNK and p38 activation in response to osmotic stress. Notably, phospho-MLK3 levels were increased in MLK4 siRNA knockdown cells that were untreated or exposed to osmotic or heat stresses, which supports previous findings that MLK4β suppresses MLK3 activation [4]. Interestingly, we observed that MLK3 is required for sorbitol, but not heat-induced activation of ERK, JNK and p-38 (Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These results indicate that MLK4 has a suppressive effect on JNK and p38 activation in response to thermostress, and ERK, JNK and p38 activation in response to osmotic stress. Notably, phospho-MLK3 levels were increased in MLK4 siRNA knockdown cells that were untreated or exposed to osmotic or heat stresses, which supports previous findings that MLK4β suppresses MLK3 activation [4]. Interestingly, we observed that MLK3 is required for sorbitol, but not heat-induced activation of ERK, JNK and p-38 (Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 90%
“…1A and B). As MLK4β suppresses MAPK signalling in certain cellular contexts, we postulated that the reduction in MLK4β might contribute to elevation inMAPK signalling in response to these stress stimuli [4]. To examine the role of MLK4β in ERK, p38 and JNK activation in response to short-term exposure to heat and osmotic stresses, RNA interference-mediated knockdown of MLK4β was performed in SKOV3 cells that were subsequently exposed to heat or treated with sorbitol for 2 h or 4 h. Cell extracts were immunoblotted for activated forms of MLK3, ERK, JNK and p38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The poorly characterized serine/threonine kinase MLK4 is abundantly expressed in various cancers (Abi Saab et al, 2012; Martini et al, 2013). Therefore, our data is applicable to other cancer types beyond GBM and provides a rationale for the therapeutic targeting of MLK4 and/or the MLK4/ NF-κB complex in a broader context.…”
Section: Discussionmentioning
confidence: 99%